The measurement by SAXS of the nematic order parameter of laponite gels - Lemaire, B.J.; Panine, P.; Gabriel, J.C.P.; Davidson, P. (Europhysics Letters, 2002)
We performed small-angle X-ray scattering (SAXS) experiments on oriented samples of laponite clay gels obtained by slow evaporation. The SAXS patterns are clearly anisotropic, which demonstrates the existence of nematic-like orientational correlations of the laponite disc-like particles. The iso-intensity lines of the SAXS patterns are elliptical and roughly homothetic over the whole scattering vector range examined in this experiment. The value of the nematic order parameter, S = 0.55 +/- 0.05, derived from the SAXS patterns is comparable to that of usual liquid crystals. This large value proves the importance of orientational correlations in these gels at concentrations higher than 0.02 g . cm(-3), even in the absence of shear.